A centric view of JAK/STAT5 in intestinal homeostasis, infection, and inflammation. (March 2021) - Surbek, Marta; Tse, William; Moriggl, Richard; Han, Xiaonan
Highlights: The review discusses major advances of JAK/STAT5 signaling in intestinal immunity. The review discusses STAT5 functions in epithelial cell repair upon injury. The review highlights gaps in the research of intestinal STAT5 function. Abstract: Cytokines, growth factors or hormones take action through the JAK/STAT5 signaling pathway, which plays a critical role in regulating the intestinal response to infection and inflammation. However, the way in which STAT5 regulates intestinal epithelial compartment is largely ignored due to the lack of genetic tools for proper exploration and because the two STAT5 transcription factors (STAT5A and STAT5B) have some redundant but also distinct functions. In this review article, by focusing on STAT5 functions in the intestinal undifferentiated and differentiated epithelia, we discuss major advances of the growth factor/cytokine-JAK/STAT5 research in view of intestinal mucosal inflammation and immunity. We highlight the gap in the research of the intestinal STAT5 signaling to anticipate the gastrointestinal explorative insights. Furthermore, we address the critical questions to illuminate how STAT5 signaling influences intestinal epithelial cell differentiation and stem cell regeneration during homeostasis and injury. Overall, our article provides a centric view of the relevance of the relationship between chronic inflammatory diseases and JAK/STAT5 pathway and it also gives an example of how chronic infection and inflammation pirate STAT5 signaling to worsen intestinal injuries. Importantly, our review suggests how to protect a wound healing from gastrointestinal diseases by modulating intestinal STAT5.